The role of opportunity-sensing and learning processes in shaping dynamic capabilities in Polish enterprises = Procesy poszukiwania okazji i uczenia się w kształtowaniu dynamicznych zdolności polskich przedsiębiorstw - Cyfert, Szymon; Krzakiewicz, Kazimierz (Zielona Góra: Faculty of Economics and Management Press)
Dynamic capabilities are an essential theoretical construct that is useful for understanding the phenomenon of competition. However, even though dynamic capabilities and issues relating to them seem to enjoy large popularity, the existing management literature lacks studies into processes that shape dynamic capabilities.
Keywords: przedsiębiorstwa polskie; zdolności dynamiczne; proces kształtowania; poszukiwanie okazji; konkurencja; uczenie się; Polish enterprises; dynamic capabilities; shaping process; sensing opportunities; competition; learning